Bosnia and Herzegovina : Technical Assistance Report-Government Finance Statistics Mission. (IMF Staff Country Reports; Country Report, 2018)
This Technical Assistance Report discusses the recommendations made by the IMF mission to assist the Central Bank of Bosnia and Herzegovina (CBBH) with the compilation of government finance statistics (GFS) in accordance with the guidelines of the Government Finance Statistics Manual 2014 (GFSM 2014) and the European System of National and Regional Accounts 2010 (ESA 2010). It was recommended that the CBBH that compiles GFS and the statistical office of the Federation of Bosnia and Herzegovina, which compiles national accounts statistics, coordinate the coding to ESA 2010. The CBBH will also examine budget items in the chart of accounts for which no unique GFS code could be assigned during the mission.